2011
DOI: 10.1007/s10552-011-9810-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium and magnesium intake in relation to cancer incidence and mortality in a German prospective cohort (EPIC-Heidelberg)

Abstract: To prospectively evaluate the associations of dietary calcium and magnesium intake with cancer incidence and mortality, data of 24,323 participants of the Heidelberg cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC-Heidelberg), who were aged 35-64 years and cancer-free at recruitment (1994)(1995)(1996)(1997)(1998), were analyzed using multivariate Cox regression models. After an average follow-up time of 11 years, 2,050 incident cancers were diagnosed and 513 cancer deaths occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 55 publications
3
42
1
Order By: Relevance
“…Vitamin E and magnesium have an anti-inflammatory effect score in the DII calculation [23]. No association was observed between magnesium and calcium and cancer-related mortality in the EPIC-Heidelberg study [68]. In a prospective study conducted by Pocobelli et al [69], vitamin E was found to significantly reduce CVD mortality; however, no association was observed with cancer mortality.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Vitamin E and magnesium have an anti-inflammatory effect score in the DII calculation [23]. No association was observed between magnesium and calcium and cancer-related mortality in the EPIC-Heidelberg study [68]. In a prospective study conducted by Pocobelli et al [69], vitamin E was found to significantly reduce CVD mortality; however, no association was observed with cancer mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies also have examined the effect of specific food items on mortality, including high-fat dairy [66,67], and nutrients such as magnesium [68], and vitamin E [69], and the results have been inconsistent. High-fat dairy is rich in saturated fat and total fat which form the pro-inflammatory components in DII calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is the lack of data on calcium supplements use in the EPIC cohort. This was however assessed in EPIC-Heidelberg, which showed that calcium supplements were used by less than 10% of subjects (42). Furthermore, results of a randomized controlled trial, investigating the risk of cancer death in over 5,000 subjects with previous fractures who were randomized to use calcium supplements, showed no association between calcium supplements use and cancer mortality (43).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] The purpose of this study was to examine the relationship between magnesium intake and the risk of CRC by undertaking a metaanalysis of prospective studies. We attempted to plan, conduct and report this meta-analysis in adherence to the guidelines of the 'Meta-analysis Of Observational Studies in Epidemiology (MOOSE) group'.…”
Section: Introductionmentioning
confidence: 99%